Folket eksisterer ikke – derfor har vi populisme. Om Laclaus populismeteori - Hansen, Allan Dreyer (Politik, 2017)
The article discusses Ernesto Laclau’s theory of populism. In Laclau, populism is not understood as a demarcated empirical phenomenon pertaining to certain political actors. It is a set of logics which mainly involve the construction of ‘the people’ in an antagonistic relation vis-a-vis ‘the elite’. Laclau’s theory is used in interpreting the Danish Social Democracy’s famous 1934 political program, Denmark for The People, and contrasted with Jan-Werner Müller’s conception of populism. The article’s main conclusion is that there are no necessary relations between democracy and populism. In other words, populism can represent both a strengthening as well as a threat to democracy.